Modulating Magnetic and Photoluminescence Properties in 2‐Aminonicotinate‐Based Bifunctional Coordination Polymers by Merging 3d Metal Ions. Issue 59 (23rd September 2020) - Pajuelo‐Corral, Oier; Zabala‐Lekuona, Andoni; San Sebastian, Eider; Rodríguez‐Diéguez, Antonio; García, Jose Angel; Lezama, Luis; Colacio, Enrique; Seco, Jose M.; Cepeda, Javier
Abstract: Herein, the synthesis and study of bifunctional coordination polymers (CPs) with both magnetic and photoluminescence properties, derived from a heterometallic environment, are reported. As a starting point, three isostructural monometallic CPs with the formula [M(μ‐2ani)2 ] n (M II =Mn (1Mn ), Co (3Co ) and Ni (4Ni ); 2ani=2‐aminonicotinate), crystallise as chiral 2D‐layered structures stacked by means of supramolecular interactions. These compounds show high thermal stability in the solid state (above 350 °C), despite which, in aqueous solution, compound 1Mn is shown to partially transform into a novel 1D chain CP with the formula [Mn(2ani)2 (μ‐H2 O)2 ] n (2Mn ). A study of the direct current ( dc ) magnetic properties of 1Mn, 3Co and 4Ni reveals a spin‐canted structure derived from antisymmetric antiferromagnetic weak exchanges along the chiral network (as confirmed by DFT calculations) and magnetic anisotropy of the ions, in such a way that long‐range ordering is observed with variable magnitude for the spin carriers. Moreover, compounds 3Co and 4Ni show no frequency‐dependent alternating current ( ac ) susceptibility curves under zero dc field; this is characteristic behaviour of a glassy state that may be partially supressed for 3Co by applying an external dc field. To overcome long‐range magnetic ordering, Co II ions are diluted in a diamagnetic Zn II ‐based matrix, which enables single‐molecule magnet behaviour. Interestingly, this strategy allows a bifunctional Co x Zn1− x 2ani material, which is imbued with a strong photoluminescent emitting capacity, as characterised by an intense blue light followed by a green afterglow, to be obtained. Abstract : Behavioural changes : The combination of 2‐aminonicotinic acid and 3d ions gives rise to a chiral 2D layered structure, showing intriguing long‐range weak ferromagnetic ordering, mainly in the case of the Co II counterpart. Long‐range ordering is suppressed by magnetically diluting the sample into a Zn II ‐based homologue, in such a way that the resulting material behaves as a bifunctional single‐ion magnet and long‐lasting phosphor.